Implementasi Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Keaktifan Berfikir Kritis Siswa dalam Mata Pelajaran Sosiologi di SMA Muhammadiyah 6 Makassar - Lukman Ismail; Yulfa Lumbaa; Egi Regita; Dahniar Nur; Fasikul Ikhsan; Muh.Ali Fikri Subair (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to increase the activeness of students' critical thinking in Sociology Learning by applying the Problem-Based Learning Model. The subjects in this study were students of class X IPS 1 at SMA Muhammadiyah 6 Makassar with a total of 17 students, consisting of 8 male students and 9 female students. The research method used in this research is descriptive qualitative using a class action research design consisting of two cycles. Data collection techniques using observation techniques, student learning outcomes tests, and field notes. In this study, a multiple choice test was conducted at the end of the cycle. The results of this study indicate that student learning outcomes in cycle I obtained an average value of 60 and an average percentage value of 60%, while the classical completeness of 60% was in the sufficient category and continued in the next cycle in cycle II action obtained an average of 83 .0, the average percentage gain is 83.0% with 90% classical completeness in the very good category. The results of the data on cycle II activities have fulfilled the KKM which has been determined by the student learning outcomes in thematic learning obtained by cycle I and cycle II indicating that there has been an average increase of 30%. Based on the research results, it can be concluded that the application of the problem-based learning model can increase the activeness of critical thinking in learning Sociology in class X IPS 1 at Muhammadiyah 6 Makassar High School in the 2022/2023 Academic Year.